Bonnesen-Style Isoperimetric Inequalities of an $n$-Simplex (Communications in Mathematical Research, 2020)
In this paper, by the theory of geometric inequalities, some new Bonnesen-style isoperimetric inequalities of $n$-dimensional simplex are proved. In several cases, these inequalities imply characterizations of regular simplex.